Investigation the Influence of SPIF Parameters on Residual Stresses for Angular Surfaces Based on Iso-Planar Tool Path - Abdulrazaq, Mustafa Mohammed; Gazi, Safaa Kadhum; Ibraheem, Marwa Qasim (Al-Khwarizmi Engineering Journal, 2019)
Incremental Sheet Metal Forming (ISMF) is a modern sheet metal forming technology which offers the possibility of manufacturing 3D complex parts of thin sheet metals using the CNC milling machine. The surface quality is a very important aspect in any manufacturing process. Therefore, this study focuses on the resultant residual stresses by forming parameters, namely; (tool shape, step over, feed rate, and slope angle) using Taguchi method for the products formed by single point incremental forming process (SPIF). For evaluating the surface quality, practical experiments to produce pyramid like shape have been implemented on aluminum sheets (AA1050) for thickness (0.9) mm. Three types of tool shape used in this work, the spherical tool gave higher residual stresses than other types, also three levels for each of step over and feed rates utilized. It found that residual stresses was raised up with increasing the step over and feed rate values, the effect of these variables studied on two slope angles. By using analysis of variance method (ANOVA) found that the most influential parameter is step over with (59.18%) and (65.42%) for both slop angles; (α=45°) and (α=55°) respectively.